(untitled) (International Journal of Physiotherapy, 2018)
Background: The fine motor skills and cognition will be reduced upon the aging. But, there is no clear idea of the association between the age-oriented reduction of cognition and fine motor skills. In this study trying to establish the relationship between the decline of cognition and fine motor skills in elderly individuals. Methods: It was an observational study performed with 45 normal elderly subjects, of which there were 23 males, 22 females, aged between 61 and 75 years. Pearson Correlation was used to find out the correlation between the data of PGI (post-graduation institute) memory scale and Purdue pegboard score, and 2-tailed t-test was used to find significant changes between data. Results: There is a statistically significant correlation (p = 0.000) between fine motor skills and the ten sub-test of Post-Graduation Institute (PGI) memory scale which explains that all the components are equally important in performing fine motor skills and the negative correlation between age with memory and fine motor skills. The positive correlation between PGI memory scale score and fine motor scores individually (p = 0.000). Conclusion: There is a positive correlation between the decline of Cognition and Fine motor skills in elderly individuals. And it proves that the changes in cognition will influence the fine motor skills.